Effectiveness Of Trademark Protection In Electronic Commerce In A Case Study Of Trademark Infringement In Indonesia - -, Andi; Setiawan, Puguh Aji Hari; Hartana, Hartana (jurnal.unprimdn.ac.id, 2026)
This study analyzes the effectiveness of trademark protection in Indonesia’s e-commerce sector amid rising digital trade and increasing infringement, including unauthorized use, counterfeiting, and consumer deception. It aims to identify causal factors and evaluate enforcement mechanisms. Using a juridical-normative method with case studies, the research examines legal documents, infringement cases, and platform-level protection policies. The findings show that although regulations such as Law No. 20 of 2016 on Trademarks and Geographical Indications and Government Regulation No. 80 of 2019 on Electronic Commerce exist, enforcement gaps persist, enabling ongoing violations. Key issues include weak supervision, inconsistent enforcement, and limited platform accountability. The study concludes that legal protection remains suboptimal due to lack of coordination among regulators, business actors, and e-commerce providers. Recommended measures include strengthening regulatory synergy, enhancing monitoring by authorities, optimizing platform-based filtering and enforcement mechanisms, and increasing legal awareness among businesses and consumers. These steps are necessary to ensure legal certainty, improve compliance, and support fair and sustainable growth of Indonesia’s e-commerce ecosystem.